Fall and Falling Fractures in the Elderly Men - Kantayaporn, MD, Choochat (Journal of Southeast Asian Orthopaedics, 2022)
Falling fracture was a common problems in elderly. This presentation aimed to identify the factors of fall and falling fracture, especially in the elderly men. The retrospective case-control study was designed. Populations from the participants of falling fracture prevention programs in Lamphun province by the year 2012 were selected. Samples were all 65 years old and above men who experienced fall within 1 year. Factors included age, body mass index, underlying diseases, chronic drugs used, history of parent fracture, steroid used, visual aquity and time up and go test were studied. Multivariate regression analysis was used. 463 cases of fall and 101 cases of falling fracture were found. Significant factors of fall in the elderly men included age, underlying diseases, history of parent fracture, steroid used, impaired visual aquity and prolong time up and go test. Significant factors of fall with fractures was only history of parent fracture. Falling fracture in the elderly men were not be influenced by intrinsic factors.